2010
DOI: 10.1007/s12665-010-0451-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pore morphology on the durability of sedimentary building stones from Aragon (Spain) subjected to standard salt decay tests

Abstract: The aim of the present article is to identify the influence of the pore morphology on the physical behaviour and durability of natural stone. Fifteen sedimentary rocks commonly used in the cultural and architectural heritage of Aragon (Spain) were characterized. The petrography, porous structure, fluid transport properties and durability of these rocks were analysed. They were classified into two different groups according to the results of the different tests. For each of these groups the physical behaviour w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The link between higher susceptibility and higher amount of microporosity has been proposed since earlier studies (Buj and Gisbert (2010) refer a publication by Russell in 1927) and there are models that relate crystallisation pressure to pore radius or pore throats (Wellman and Wilson 1965;Fitzner et al 1996;Scherer 1999Scherer , 2004Steiger 2005b;Ruedrich et al 2007;Espinosa Marzal and Scherer 2008;. Hence, another kind of durability estimators considers microscopic characteristics (usually measured by mercury injection porosimetry) related to pore-size distribution (Rossi-Manaresi and Tucci 1991;La Iglesia et al 1997;Ordóñez et al 1997;Gauri and Bandyopadhyay 1999; or combination of macroscopic and microscopic parameters of the pore space (Miglio et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The link between higher susceptibility and higher amount of microporosity has been proposed since earlier studies (Buj and Gisbert (2010) refer a publication by Russell in 1927) and there are models that relate crystallisation pressure to pore radius or pore throats (Wellman and Wilson 1965;Fitzner et al 1996;Scherer 1999Scherer , 2004Steiger 2005b;Ruedrich et al 2007;Espinosa Marzal and Scherer 2008;. Hence, another kind of durability estimators considers microscopic characteristics (usually measured by mercury injection porosimetry) related to pore-size distribution (Rossi-Manaresi and Tucci 1991;La Iglesia et al 1997;Ordóñez et al 1997;Gauri and Bandyopadhyay 1999; or combination of macroscopic and microscopic parameters of the pore space (Miglio et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, another kind of durability estimators considers microscopic characteristics (usually measured by mercury injection porosimetry) related to pore-size distribution (Rossi-Manaresi and Tucci 1991;La Iglesia et al 1997;Ordóñez et al 1997;Gauri and Bandyopadhyay 1999; or combination of macroscopic and microscopic parameters of the pore space (Miglio et al 2000). However, Buj and Gisbert (2010) proposed that stones with high microporosity (and low porosity) could be more durable in salt weathering conditions as a result of low connectivity and high tortuosity of the pore space.…”
Section: Introductionmentioning
confidence: 99%
“…The salt-crystallisation ageing test has not been performed in this study, but a high degree of resistance of the studied rocks to salt decay phenomena can be predicted from the low porosity and the type of the pore size distribution of these rocks, as previously reported (e.g., Buj and Gisbert, 2010;Everett, 1961;Honeyborne and Harris, 1958). The latter authors demonstrated that rocks with a high percentage of pore throats radii < 0.1 mm are less susceptible to salt decay than rocks with higher pore size.…”
Section: Discussionmentioning
confidence: 50%
“…The total porosity for all lithotypes ranges between 2 and 4%, whereas a majority of pore size radii are < 0.1 mm. This kind of pore size distribution induces a very slow dynamic mobility of solutions inside the rock (Benavante, 2011;Buj and Gisbert, 2010;McGreevy, 1996;Pé dro, 1983Pé dro, , 1993Pé dro and Delmas, 1983;Ruedrich and Siegesmund, 2007). The secondary porosity created by dissolution is mostly closed as suggested by the low values calculated by MIP and by the hydrostatic method.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, different kinds of synthetic copolymers have been widely employed on stone buildings as adhesives, consolidants and surface protectives of cultural heritages [8][9][10][11]. Acrylic resins were usually be used for protecting the stone building by coating on it.…”
Section: Introductionmentioning
confidence: 99%